(untitled) (African Journal of Science, Technology and Social Sciences, 2022)
Child Sexual abuse (CSA) is both a social and public health concern worldwide. It is often associated with a number of deleterious psychological and behavioural outcomes for survivors. A mutual misapprehension about CSA is that it is a rare act perpetrated against girls by male strangers. In spite of a surfeit of research on CSA, little is known on the resilience process among the children survivors. In the recent past in Kenya, sexual abuse has been noted in schools most of which the perpetrators go scot-free. It occurs at all levels of society and affects not only girls but also boys in all levels of the society. The purpose of this study therefore was to explore the resilience process among the sexually abused children who form part of the vulnerable groups in Kisii County. The study utilized descriptive survey design. The sample size was 100 pupils, 100 parents,10 Key Informants and 10 practicing Social workers. The findings of the study reveal that in order to curb child sexual abuse, the risk factors such as poverty, parental negligence and harmful traditional cultural practices should be addressed. The Social workers also need to take up their roles in the prevention, restoration and resource provision to curb CSA. The study recommends on psycho-social therapy, cognitive behavioral therapy, offender registration, community notification, and mandatory background check for teachers, residency restriction and sentence lengthening as a mitigation strategy to ending sexual violence against pupils.